Electrochemical Study of the Reduction of Manganese (III) by Rotating Disc Voltammetry in Non-aqueous Solvents - A. Abeed, F.; Sh. Ahmed, K. (Asian Journal of Chemistry, 2010)
The voItammetric behaviour of the Mn(III) has been examined at rotating disc electrodes of silver, gold and glassy carbon electrodes in dimethylforamide (DMF), acetonitrile (ACN) , ethanol (EtOH) and methanol (MeOH). Cathodic reduction of Mn(III) displayed a single well-defined cathodic wave and obeyed the Levich plots at all electrodes and solvents studied. The limiting current is linearly proportional to concentration affording an excellent and rapid determination of Mn(III). The electrode kinetic parameters, conditional potentials have been determined and the effects of the solvents on these parameters have been explored.